Status of the RODOS system for off-site emergency management after nuclear and radiological accidents and its enhancement under the EURANOS project. (14th January 2008) - Raskob, W.; Ehrhardt, J.
Under the auspices of its Euratom Research Framework Programmes, the European Commission (EC) has supported the development of the RODOS (Real-time On-line DecisiOn Support) system for off-site emergency management after nuclear accidents. The current version of the system has been, or is being, installed in many national emergency centres. RODOS provides coherent support at all stages of an accident (i.e., before, during and after a release), including the long term management and restoration of contaminated areas. The system is able to support decisions about the introduction of a wide range of potentially useful countermeasures (e.g., sheltering and evacuation of people, distribution of iodine tablets, food restrictions, agricultural countermeasures, relocation, decontamination, restoration, etc.) mitigating the consequences of an accident with respect to health, the environment, and the economy. Within the EURANOS project, the RODOS system will be further enhanced for practical applicability in operational emergency centres.